Light - Harrison, M. John 1945- (Bantam books, 2004)
Michael Kearney, a British scientist, and his American partner, Brian Tate, unknowingly become the fathers of interplanetary travel while studying laboratory quantum physics. Kearney is also a serial killer who is on the run from the entity that drives him to kill.
Keywords: Serial murderers -- Fiction; Space and time -- Fiction; Science fiction